PENGEMBANGAN SISTEM BASIS DATA PRESENSI PERKULIAHAN DENGAN KARTU MAHASISWA BER-BARCODE - Abdul Fadlil; Kartika Firdausy; Fauzi Hermawan (Universitas Ahmad Dahlan, 2008)
The level of attendance in an institution is very important because the credibility of a person seen from the high level of diligent presence or absence of the person. Like for example in activities at a university, data on the level of attendance of a student in a lecture to be very important because there are professors that considers presence as one of the components in the assessment. However, the system manually presence there it is less effective in storing the data. This study aims to design a system using barcode presence as presensinya data input. Presence system design includes three components namely the barcode found on the student card, barcode scanners Series CD-108E CCD (CCD scanner) and the computer. Attendance management through this system enables the optimization function Student Identity Card (KTM) equipped with a Student Identification Number. Use of this system will facilitate the presence to monitor student attendance mengontrolan the student. Presence system has been tested with several different variations of the KTM through the distance and position of the barcode on the barcode scanner. Test results obtained ideal position to barcode scanners barcode reading is at a distance of 2 cm with an accuracy rate of 100% and at an angle of 900 accuracy rate of 100%.